Proceedings: workshop on water quality monitoring in Colorado - Ward, Robert C., editor; Raley, William L., editor; Colorado Water Resources Research Institute, Colorado State University, publisher (Colorado State University. Libraries, 1985)
Workshop on Water Quality Monitoring in Colorado (1985: Colorado State University).
Workshop on water quality monitoring in Colorado
July 1985.
Keywords: Water-supply -- Colorado; Water -- Pollution -- Colorado; Water -- Composition